The development of teachers' visions from preservice into their first years teaching: A longitudinal study. (May 2017) - Parsons, Seth A.; Vaughn, Margaret; Malloy, Jacquelynn A.; Pierczynski, Melissa
Abstract: Contemplating and articulating one's vision is a reflective process that guides teachers' instruction and professional development. However, little research has explored how teachers develop their visions from preservice preparation to their first years teaching. The current study describes the visions of nine teachers over the course of seven years. The researchers describe teachers' visions, how the teachers enacted their visions, affordances to enacting their visions, obstacles teachers faced to enacting their visions, and how teachers' negotiated obstacles to enact their visions. Findings demonstrate the stability and influence of teachers' visions and the multitude of factors that impact teachers' daily decisions. Highlights: Teachers' visions focused on developing motivated and successful students. Affordances to enacting visions included a supportive school and experience. Obstacles to enacting visions included policy mandates and meeting diverse needs. Negotiations of obstacles included instructional adaptations and going rogue.